Rationality is not coherence - Heinzelmann, Nora (The philosophical quarterly, 2024)
According to a popular account, rationality is a kind of coherence of an agent’s mental states and, more specifically, a matter of fulfilling norms of coherence. For example, in order to be rational, an agent is required to intend to do what they judge they ought to and can do. This norm has been called ‘Enkrasia’. Another norm requires that, ceteris paribus, an agent retain their intention over time. This has been called ‘Persistence of Intention’. This paper argues that thus understood norms of rationality may at times conflict. More specifically, Enkrasia and Persistence of Intention may place demands on the agent that are impossible to fulfil. In these cases, the framework of requirements does not provide us with norms that make us rational. A rival account, according to which rationality is a kind of responsiveness to one’s available reasons, can overcome the problem.